Pre-competition anxiety and its correlation with front handspring on vault table among junior gymnasts - Shaman, Aasaad J.; Kadhim, Abdullah Ab.; Jameel, Abdulazeez N. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The present study was conducted to identify the level of anxiety and its relationship with front handspring on vault table among junior gymnasts in Nasiriyah club. The study also aimed to identify the statistical differences in performing this skill according to the variables and training conditions. A total of 20 gymnasts were recruited from the junior club of Nasiriyah by random sampling method. The measurement of anxiety among the athletes was done by a questionnaire, developed by Allawi in 1998. The findings of the present study revealed a significant correlation between pre-competition anxiety and the performance of a front handspring on the vault table among gymnasts in Nasiriyah junior club.